2019
DOI: 10.3892/ol.2019.10591
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA‑CCDC26, as a novel biomarker, predicts prognosis in acute myeloid leukemia

Abstract: The aim of the present study was to examine the expression and clinical significance of long non-coding RNA (lncRNA)-CCDC26 in patients with acute myeloid leukemia (AML), and to investigate the potential functions of CCDC26. The Gene Expression Omnibus database and reverse transcription-quantitative polymerase chain reaction analysis were used to detect the expression levels of CCDC26 in patients with AML and healthy volunteers. Clinical data for 93 patients with AML were collected to analyze the clinical sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Subsequently, researchers found that lncRNA CCDC26 level in patients with AML was significantly associated with age, anemia, risk stratification, and remission. Furthermore, the overall survival of AML patients with a high expression level of lncRNA CCDC26 was poor ( P = 0.0105) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, researchers found that lncRNA CCDC26 level in patients with AML was significantly associated with age, anemia, risk stratification, and remission. Furthermore, the overall survival of AML patients with a high expression level of lncRNA CCDC26 was poor ( P = 0.0105) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous lncRNAs are deregulated in different sorts of malignant growths, including head and neck cancer [92]. Unmistakable expression profiles of lncRNA have been distinguished in leukemia [9,33,35,45,[47][48][49][93][94][95][96][97][98][99]. Some of these have been demonstrated to have wellunderstood jobs in the development and progression of leukemia, suggesting the vital use of lncRNAs as novel biomarkers and potential targets for the treatment of leukemia.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…A total of 7444 lncRNAs (3606 known and 3838 novel lncRNAs) were identified as eRNAs by comparing the genomic coordinates of lncRNAs overlapped with the known enhancer regions from Ensembl and VISTA enhancer databases. For example, lncRNA CCDC26 was found to be a novel biomarker in acute myeloid leukemia and also found to control myeloid leukemia cell growth ( 50 , 51 ). Using our in silico analysis method, we discerned that CCDC26 is nearby (enhancer of the gene) the hs1709 (VISTA ID) enhancer region.…”
Section: Resultsmentioning
confidence: 99%